Molecular evidence of a new Babesia sp in goats - Ozubek, Sezayi; Aktas, Munir (Elsevier, 2017)
In this study, a novel Babesia sp. infecting goats was detected and its phylogenetic relationship to related species was determined. A total of 200 blood samples collected from sheep (n = 78) and goats (n = 122) were examined in the study. The V4 hypervariable region of the 18S rRNA gene of the novel Babesia sp. was amplified by PCR and analysed using a reverse line blot hybridization assay adapted for small ruminants. Samples from seven goats hybridized to TheileriajBabesia catch-all and Babesia catch-all probes and did not hybridize to any species-specific probe tested, suggesting the presence of an unrecognized Babesia species or genotype. Sequencing results showed the isolate to clearly differ from ovine Babesia species and genotypes currently available in the GenBank database. The isolate showed 90.9%, 93.5%, and 93.4% identity to B. ovis, B. motasi, and B. crassa, respectively and 91-93% similarity to Babesia genotypes recently described in small ruminants. The highest homology (similar to 96-97%) observed was with Babesia odocoilei, Babesia sp. EU1, and Babesia divergens. The new isolate was provisionally designated Babesia sp. The study contributes to better insight into the distribution and phylogenetic diversity of piroplasms in small ruminants. The survey indicated a high prevalence of piroplasms in small ruminants (21.5%). Of those detected, T. ovis was the most prevalent (17%), followed by Babesia sp. (3.5%), and B. ovis (2%). (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Theileria; Babesia; PCR; Reverse line blot; Sheep; Goats